Designing for the disabled in Malaysian environment - Tang, Teong Kuok (1981)

(untitled)
In most countries, it has been estimated that 1O% of the total population can be categorised under "The Disabled". With such percentage and its existence in our society, one should not deny the importance of desinging for the disabled which has been studied in other countries but not Malaysia. 'Thus, the topic "DESIGNING FOR THE DISABLED IN ENVIRONMENT is chosen for final year paper, PBP461: Student Initiated Research Project, in partial fulfilment of the requirements for the degree of Bachelor of Science (Housing, Building and Planning). It is also chosen bearing in mind the following aims :